Causes and Contaminants of Soils and Water in the Niger Delta Region of Nigeria: A Systematic Review - Emmanuel, Dada Ayomikun; Udi, Emoyoma Ogheneovoh; Orji, Maureen C. (British Journal of Healthcare and Medical Research, 2025)
Contaminants of various sources and types constitute a great environmental nuisance to many oil producing regions of the world, and the Niger Delta region of Nigeria is no exception from this menace. This has negatively impacted the region, posing a lot of health and environmental risks to the inhabitants. Hence, in the quest to ascertain the causes and common contaminants of soils and water in the region, a systematic review was conducted across three academic databases (PubMed, Scopus and Web of Science) by two independent reviewers within a five-year period (2020-2025). Keywords, synonyms, Boolean search strings as applicable and the Preferred Reporting Items for Systematic Review and Meta-analyses (PRISMA) was used. A total of 533 articles were obtained from the initial search which were later filtered down to 393 articles using specific inclusion criteria, language and journal publication filters. Further screening using additional keywords and abstract preview reduced the set to 131 and subsequently 23 articles included in this systematic review. The reviewed articles revealed that contaminants from the Niger Delta region could be classified into five categories which are heavy/trace metals (Cd, Pb, Cr, Ni, Cu, Zn, Fe, Mn, As and Ba), Petroleum-related hydrocarbons and Polycyclic Aromatic Hydrocarbons (PAHs), BTEX and Total Petroleum Hydrocarbons (TPHs), Persistent Organic Pesticides (POPs) and microbial contamination. Unfortunately, anthropogenic activities which include indiscriminate waste disposal, spills from oil and gas exploration activities, spillage from petroleum tankers and vandalised pipelines, waste and spent oil from mechanic workshops and agricultural runoffs were implicated as the causes of these pollution. Hence, this review recommends extensive enlightenment and mass awareness as a crucial part of addressing contaminations and environmental degradation within the Niger Delta region.